CONTINUITY IN THE TRANSITION FROM PRESCHOOL TO PRIMARY EDUCATION: ASPECTS OF CONTENT AND OUTCOME (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
The transition from preschool to primary education is a crucial stage in a child’s cognitive, emotional, and social development. Ensuring continuity between educational programs and aligning the content and outcomes of learning supports the child’s successful school adaptation, personal growth, and preparation for further education. Skills and knowledge acquired in preschool should continue to develop throughout primary education.